Implementation of the Health Belief Model to Predict Acupuncture Therapy Adherence in Patients with Hernia Nucleus Pulposus - Afifah Kusumaning Tyas; Bhisma Murti; Ika Sumiyarsih Sukamto; Hanung Prasetyo; Setyo Sri Rahardjo; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Hernia Nucleus Pulposus is one of the causes of low back pain that can interfere with activity and quality of life. Acupuncture therapy is one of the effective non-pharmacological treatment alternatives in reducing pain due to Hernia Nucleus Pulposus. However, patient adherence to undergoing acupuncture therapy is still a challenge. This study aims to analyze the factors within the framework of the Health Belief Model that affect adherence to acupuncture therapy in patients with Hernia Nucleus Pulposus. Subjects and Method: This study was a cross-sectional study conducted in Surakarta, from January to March 2025. A total of 200 patients were selected randomly. The dependent variable was adherence to acupuncture therapy in Hernia Nucleus Pulposus. Independent variables were perceived susceptibility, perceived severity, perceived benefits, perception of barriers, self-efficacy, and cues to action. The data were analyzed using Linear Regression. Results: Adherence to acupuncture therapy patients with hernia nucleus pulposus increased with high perceived susceptibility (b=0.14; 95% CI= 0.01 to 0.27; p= 0.040), high perceived severity (b= 0.30; 95% CI= 0.02 to 0.59; p=0.038), high perceived benefits (b= 0.16; 95% CI= 0.01 to 0.31; p=0.042), high cues to action (b=0.19; 95% CI= 0.02 to 0.36; p= 0.032), high self-efficacy (b=0.19; 95% CI= 0.02 to 0.38; p= 0.022). Adherence to acupuncture therapy decreased with high perceived barrier (b= -0.10; 95% CI= -0.21 to -0.01; p= 0.046). Conclusion: There was a positive relationship between perceived susceptibility, perceived severity, perceived benefits, cues to action, and self-efficacy on adherence to acupuncture therapy. Perceived barriers decrease adherence to acupuncture therapy in hernia nucleus pulposus.